TINDAK PIDANA KEKERASAN FISIK MENGAKIBATKAN KEMATIAN DALAM LINGKUP RUMAH TANGGA (PUTUSAN NO.27/PID.B/2021/PN.TRT) - Nurul 'Arifah Dharmaningtyas; Vientje Ratna Multiwijaya (Fakultas Hukum Universitas Trisakti, 2022)
Criminal acts regarding a violence or abuse in a household matters are included in 2 (two) laws, which is the Criminal Code which has a public characteristic and Law number 23 of 2004 that has a specific characteristic. The main research’s problem are: whether the Defendant's actions is in accordance with Article 354 paragraph (2) in conjunction with Article 356 1 of the Criminal Code (Decision Number 27/Pid.B/2021/PN.Trt) and the punishment of the perpetrators of physical violence that resulting in death within the household (Decision Number 27/Pid.B/2021/PN.Trt). The research conducted in normative and descriptive analytical legal research, using secondary data obtain through library research. The data is analyzed qualitatively and the conclusions are drawn using deductive method. The actions of the perpetrator in this case constituted an act of physical violence resulting in death within the household that is in accordance with Article 44 paragraph (3) of Law no. 23 of 2004. The sentencing of the perpetrators is in accordance with sentencing theories.